Distinct microglial and macrophage distribution patterns in the concentric and lamellar lesions in Baló's disease and neuromyelitis optica spectrum disorders. (23rd September 2020) - Hayashida, Shotaro; Masaki, Katsuhisa; Suzuki, Satoshi O.; Yamasaki, Ryo; Watanabe, Mitsuru; Koyama, Sachiko; Isobe, Noriko; Matsushita, Takuya; Takahashi, Kazuya; Tabira, Takeshi; Iwaki, Toru; Kira, Jun‐ichi
Abstract: TMEM119 and purinergic receptor P2Y12 (P2RY12), which are not expressed by recruited peripheral blood macrophages, are proposed to discriminate microglia from macrophages. Therefore, we investigated the distribution patterns of microglia and macrophages in 10 concentric lesions from four autopsied Baló's disease cases and one neuromyelitis optica spectrum disorder (NMOSD) case, using quantitative immunohistochemistry for the markers TMEM119, P2RY12, CD68, CD163 and GLUT5. Three cases with Baló's disease had distal oligodendrogliopathy (DO) showing preferential loss of myelin‐associated glycoprotein and early active demyelination in the outermost demyelinating layer (termed DMY‐MO). In DMY‐MO with DO, TMEM119‐positive activated microglia expressing upregulated GLUT5 but markedly downregulated P2RY12 were significantly increased. These activated microglia expressed inducible nitric oxide synthase. Oligodendrocytes and their precursors showed apoptotic‐like nuclear condensation in DMY‐MO. TMEM119‐negative and CD68/CD163‐positive macrophages were distributed throughout the lesion center of DMY‐MO with DO and these cells demonstrated foamy morphology only in the inner portion but not in the outer portion. In concentric demyelinating lesions from another Baló's case and lamellar demyelinating lesions in an NMOSD case, which had late active demyelination without DO, the densities of TMEM119‐, GLUT5‐ and P2RY12‐positive microglia with ramified morphology were significantly increased in myelinated layers but not in demyelinating layers. In particular, in the NMOSD case, TMEM119‐positive microglia were confined to the outer portion of the myelinated layers. CD68‐positive macrophages with foamy morphology also expressing CD163 accumulated in myelinated as well as in demyelinated layers. These findings suggest that activated microglia expressing TMEM119 and GLUT5, but not P2RY12, are associated with apoptosis of oligodendrocytes in the leading edge of Baló's concentric lesions with DO, whereas TMEM119‐, GLUT5‐ and P2RY12‐positive microglia with ramified morphology are associated with myelin preservation in concentric lesions without DO in Baló's disease and NMOSD. These two types of microglia appear to play distinct roles in the formation of concentric lesions. Abstract : Hayashida et al. discriminated the distribution pattern of microglia and macrophages in concentric and lamellar lesions in Baló's disease and neuromyelitis optica spectrum disorders. Activated microglia expressing TMEM119 and GLUT5, and lacking P2RY12, may play a critical role in the evolution of demyelinating layers in Baló's disease. GLUT5 in microglia might be a potential therapeutic target for demyelinating diseases.